Clinical research in renal transplantation: a bibliometric perspective on a half-century of innovation and progress - Jiang, Decan; Mantas, Anna; Studier-Fischer, Alexander; Fuchs, Juri; Uluk, Deniz; Loos, Martin; Mieth, Markus; Zeier, Martin; Husen, Peri; Golriz, Mohammad; Kahlert, Christoph; Ryschich, Eduard; et al. (Transplantation, 2024)
Background: Groundbreaking biomedical research has transformed renal transplantation (RT) into a widespread clinical procedure that represents the mainstay of treatment for end-stage kidney failure today. Here, we aimed to provide a comprehensive bibliometric perspective on the last half-century of innovation in clinical RT. Methods: The Web of Science Core Collection was used for a comprehensive screening yielding 123 303 research items during a 50-y period (January 1973-October 2022). The final data set of the 200 most-cited articles was selected on the basis of a citation-based strategy aiming to minimize bias. Results: Studies on clinical and immunological outcomes (n = 63 and 48), registry-based epi research (n = 38), and randomized controlled trials (n = 35) dominated the data set. Lead US authors have signed 110 of 200 articles. The overall level of evidence was high, with 84% of level1 and -2 reports. Highest numbers of these articles were published in New England Journal of Medicine, Transplantation, and American Journal of Transplantation. Increasing trend was observed in the number of female authors in the postmillennial era (26% versus 7%). Conclusions: This study highlights important trends in RT research of the past half-century. This bibliometric perspective identifies the most intensively researched areas and shift of research interests over time; however, it also describes important imbalances in distribution of academic prolificacy based on topic, geographical aspects, and gender.